Implementasi Kebijakan Pengelolaan Hibah Dan Bantuan Sosial Kota Bekasi (Studi Tentang Implementasi Peraturan Menteri Dalam Negeri Nomor 32 Tahun 2011 Tentang Pedoman Pemberian Hibah dan Bantuan Sosial Yang Bersumber Dari Anggaran Pendapatan dan Belanja Daerah) - Widodo Indrijantoro; Iwan Irwansyah; Redo Alpha Hernando; Biyan Sukeri (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2021)
Grant Expenditures must be managed in an orderly manner, obeying laws and regulations, efficient, economic, effective, transparent and accountable by taking into account the principles of justice, appropriateness, rationality and benefits for the community. This is intended to create administrative order, accountability, transparency in the management of grant funds and accuracy in the use of aid funds by grant recipients. The formulation of the problem discussed in this study is how to manage grants and social assistance for the Bekasi City Govemment. The research method used is descriptive qualitative research, which is the process of organizing and sorting data into patterns and categories as well as basic description units so that themes can be put forward as suggested by the data. The results of the research are that the management of grants and social assistance funds in Bekasi City was not properly implemented in 2018. It was explained that this study did not use population and samples but key informants and respondents. Researcher determines the Regional Work Unit (SKPD) for Grants and Social Assistance as Key Informants which in this study are represented by the Manager of Grants and Social Assistance in each SKPD. Meanwhile, the respondents were several people who were taken from the Advisory Team for grants and social assistance. Research results, researcherconcluded that the management of grants and social assistance at the Bekasi City Regional Financial and Asset Management Agency in 2018 had not been carried out properly. Some of the obstacles to the management of grant funds and social assistance in Bekasi City are the lack of available personnel, staff who have not received training regarding grant aid management, incomplete rules and procedures for managing grant funds, and overlapping allocations of funds in grant expenditure.